A Study of UNIMEN Students' Perspectives on Cross-Cultural Adaptation in Thailand - Mustakim, Mustakim; Astri, Zul; Baharuddin, Andi Farid; Isma, Adi; Noer, Fhadli (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
This study explores the perspectives of Universitas Muhammadiyah Enrekang (UNIMEN) students on cross-cultural adaptation during their international internship in Thailand. Community service programs, which are mandatory for Indonesian tertiary students, offer practical experiences that bridge the gap between academic learning and real-world application. This research focuses on the challenges and adaptation strategies employed by students participating in teaching practices at private Thai schools. Using a qualitative methodology and thematic analysis, data were collected through interviews with eight fifth-semester students majoring in English Language Education. The findings identify eight key challenges: administrative issues, health problems, psychological stress, social integration difficulties, teaching challenges, culture shock, language barriers, and inadequate facilities. Cultural barriers, such as differences in the education system and social norms, led to experiences of homesickness and stress. Language difficulties were particularly pronounced due to limited Thai and English proficiency among locals. To address these challenges, students adopted several strategies, including seeking social support, engaging in cultural learning, using sign language, and fostering communication with locals. These strategies helped alleviate culture shock, improve cross-cultural understanding, and enhance teaching effectiveness. The study underscores the importance of adequate preparation, including cultural learning modules, and provides valuable insights for universities to better support future participants in international community service programs.